2015
DOI: 10.1063/1.4931632
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of long lifetimes in Cu(In,Ga)Se2 by time-resolved photoluminescence

Abstract: The main objective of time-resolved photoluminescence (TRPL) is to characterize minority carrier recombination in semiconductors. However, trap states in the band gap can lead to artificially long decay times thus distorting the measured minority carrier lifetime. In this work, we propose to measure TRPL under elevated temperature and excitation in order to reduce minority carrier trapping. Taking three Cu(In,Ga)Se2 layers as examples, we show that the decay time decreases with increasing temperature—in accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 28 publications
2
20
1
Order By: Relevance
“…4) and use TCAD modeling to evaluate device performance. In contrast to reported results measured on CIGS solar cells fabricated by an industrial process 21 , no strong variation in lifetime is observed at temperatures near 300 K. In addition, the TRPL data for the high-efficiency solar cells studied here can be fully described with a single-exponential decay model. This leads us to conclude that minority-carrier trapping in shallow states is not a significant contributor to recombination in our samples.…”
Section: Discussion and Device Modelingcontrasting
confidence: 76%
“…4) and use TCAD modeling to evaluate device performance. In contrast to reported results measured on CIGS solar cells fabricated by an industrial process 21 , no strong variation in lifetime is observed at temperatures near 300 K. In addition, the TRPL data for the high-efficiency solar cells studied here can be fully described with a single-exponential decay model. This leads us to conclude that minority-carrier trapping in shallow states is not a significant contributor to recombination in our samples.…”
Section: Discussion and Device Modelingcontrasting
confidence: 76%
“…On the other hand, the quenching of the band-edge PL lifetime appears rather contradictory to the steady-state PL results that indicate a monotonic increase in the integrated PL intensity as deposition temperature is increased up to 500°C. Furthermore, the average PL lifetime values obtained for the band-to-band peak 3 appear reasonable only for CIGS500°C, being comparable to values reported in literature for high quality CIGS thin films [16,17] while the dynamics of such peak appear significantly inflated for the CIGS300°C and CIGS400°C films.…”
Section: Resultssupporting
confidence: 86%
“…The obtained decays can now be adequately fitted using double-exponential decays, with a long lifetime of hundreds of ns and a significant shorter decay of the order of few to tens of ns. It is evident that the method introduces a large statistical uncertainty in the extracted decay lifetimes due to the small density of experimental data but circumvents the significant systematic error produced by the spectral overlap of the Gaussian peaks; the validity of the method has been demonstrated in previous work of some of the manuscript authors on probing the dynamics of multi-component emission with overlapping peaks [16,18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular the measured decay time can be much longer than the lifetime due to trapping and detrapping effects [93]. The influence of detrapping effects can be detected by the temperature dependence of the decay behaviour [94]. The temperature dependence of the detrapping effect can be developed into a method to characterise the trap states themselves [95].…”
Section: à3mentioning
confidence: 99%